Power and gender in UK defence - Dunn, Michael D. (Svenska handelshögskolan, 2010)
This paper examines the position of women in the UK Armed Forces, from the viewpoint of the authority they exercise. For that reason it focuses on the officer cadre. It presents a literature review on this important aspect of the gender debate eg Goldstein (2001), Van Creveld (2001). It also examines the issues of power and authority within military organisations, and identifies that authority flows from the top through the military command concept (Watters 2004). It then reviews comparative empirical data on the number of men and women officers employed, and their rank using the generic NATO rank structure. It also analyses their employment within each service: Army, Naval Service and Royal Air Force (MOD 2009). Using a weighted model, derived mainly from the typical size of a command group at each rank, it assesses the contribution to authority, and therefore leadership contribution, that women exercise. The model identifies that women exercise virtually no authority because, although they form a significant percentage of the officer cadre overall (12%), this attenuates up the rank structure, almost to zero at the most senior levels. It also reviews the current operational context and range of conflicts in which women serve, eg Iraq and Afghanistan and the impact of current UK Ministry of Defence (MOD) deployment policy on women’s career prospects. Building on earlier research (Dunn 2008), the paper finds that the role of women remains conflicted with increasing levels of exposure to death or injury, but limited career prospects. The paper then discusses the consequences of this situation and the appropriate research response.